Impact of total ischaemic time and disease severity class on graft function after bilateral lung transplantation - Aburahma, Khalil; Manna, Nunzio D. de; Boethig, Dietmar; Franz, Maximilian; Iablonskii, Pavel; Heise, Emma L; Bobylev, Dmitry; Avsar, Murat; Greer, Mark; Schwerk, Nicolaus; Sommer, Wiebke; Welte, Tobias; et al. (European journal of cardio-thoracic surgery, 2023)
Total ischaemic time (IT) is considered a limiting factor in lung transplantation. In this retrospective study, we investigate effects of IT and disease burden on outcomes after bilateral lung transplantation.A total of 1298 patients undergoing bilateral lung transplantation between January 2010 and May 2022 (follow-up 100%, median 54 months) were included. Pre-transplant diseases’ severity (recipient body mass index, recipient age, previous lung transplantation, Tacrolimus immunosuppression, preoperative recipient extracorporeal membrane oxygenation support, lung volume reduction) for graft failure was individually calculated and—as IT—categorized. Vice versa adjusted Cox models were calculated. Considering competing risks, we assessed cumulative incidences of airway obstructive complications and chronic lung allograft dysfunction with death as competing risk factors for primary graft dysfunction were assessed by binary logistic regression.Higher disease burden significantly accelerated chronic lung allograft dysfunction and death occurrence (P < 0.001); IT did not. IT-adjusted disease burden strata showed 50% graft survival differences at 11 years after transplantation (range 24-74%), disease burden-adjusted IT strata 18% for all and 6% (54-60%) among those above 7 h. All significant primary graft dysfunction risk factors were diagnoses related, IT was not significantly important and odds ratios did not increase with IT.The eventual graft survival disadvantage that results from an IT between 7 and at least 11 h is negligible in contrast to frequent recipients’ disease-based risk levels.